The EDSA Republic as Moral Liquidator Embedded Origins, Unintended Consequences - Cardenas, Kenneth (2024)
This article revisits the privatizations carried out after the People Power Revolution, and how a moralized understanding of the state’s role in the economy was rehearsed and developed by the revolutionary Corazon Aquino government (1986–1987) through the reorganization of the government-owned or -controlled corporation portfolio. It traces how the design and objectives of privatization reflected both “people-powered” ambitions, as well as a distinct, historically embedded ambivalence toward public enterprise. In turn, these departures from mainline neoliberalism shaped a key feature of the EDSA Republic: the continuity of rentierism as the dominant mode of accumulation, despite the apparent rupture of revolution.
Keywords: Government-Owned and Controlled Corporations; Government business enterprises -- Philippines; Presidential Commission on Government Reorganization (PCGR); Privatization; Neoliberalism